Microbial profile and antibiotic resistance patterns of organisms causing venous catheter infections in hemodialysis units - Aamir, Muhammad; Anam, Namra; Muneeb, Muhammad Yasir; Imran, Muhammad; `Qaisar, Fahad; Javaid, Ayesha (Infectious Diseases Journal of Pakistan, 2025)
Background: Central venous catheters (CVCs) are widely used in hemodialysis but predispose patients to catheter-related bloodstream infections (CRBSIs). This study evaluated microbial patterns, antibiotic resistance, and risk factors of CRBSIs in tunneled CVCs at a tertiary care hospital. Material and Methods: Cross-sectional analytical study was conducted from January to June 2025 at hemodialysis unit of Bahawal Victoria Hospital, Bahawalpur. Total 340 adult patients with tunneled CVCs and clinical signs of CRBSI were enrolled. Confirmed CRBSI was defined by CDC/CLSI criteria using differential time to positivity or semi-quantitative catheter tip culture. Blood and catheter tip samples were processed for microbial identification and antimicrobial susceptibility testing. Data were analyzed using SPSS version 23.0. Results: Only 32 patients (9.4%) had confirmed CRBSI. Gram-positive bacteria predominated (70.6%) with Staphylococcus aureus (38.2%) and coagulase-negative staphylococci (26.5%) as the leading pathogens. Gram-negative bacteria (23.5%) included Klebsiella pneumoniae and Pseudomonas aeruginosa. Fungal infections (5.9%) were due to Candida albicans. High resistance rates were observed: 61.5% of S. aureus were MRSA, 77.8% of CoNS were methicillin-resistant and 50.0% of Gram-negative isolates were ESBL producers. A catheter dwell time >6 months was significantly associated with CRBSI (p < 0.001). Conclusion: Despite a low confirmed CRBSI rate the high prevalence of multidrug-resistant organisms among confirmed cases highlights critical need for accurate diagnosis and antimicrobial stewardship. Prolonged catheter use is a key modifiable risk factor. Keywords: Candida albicans, Catheter-related bloodstream infection, Central venous catheter, Drug resistance, microbial, Pseudomonas aeruginosa, Staphylococcus aureus.